Optimasi Pembangkit Hybrid Energi Terbarukan Pada Kampus Vokasi ATS Menggunakan Metode Wild Horse Optimization (WHO) - Marliani Marliani; Muhammad Naim; Abdul Tahir (Pusat Riset dan Inovasi Nasional, 2025)
The use of renewable energy sources has become widespread throughout the world as a step to reduce dependence on fossil energy. Hybrid electric power systems that use renewable energy as their base have been adopted as a solution to produce energy efficiently. In this paper, the hybrid system discussed is hybrid PV, wind turbine and battery storage. This hybrid design system is very dependent on the load profile, potential energy sources, and geographical location of the research location. This research discusses the technical design and capital costs of a hybrid electric power system which will be implemented as a practicum alternative energy source on the ATS campus, Sorowako. Irradiance, temperature, average wind speed and component sizing are the main parameters discussed. Design technical and economic analysis (capital cost) using MATLAB software with the wild horse optimization (WHO) algorithm. The results of the WHO analysis will be compared with the analysis of a common optimization method, namely PSO. And the results obtained from the WHO and PSO analyzes are not much different, but the WHO analysis reaches its convergence value faster, namely in the 20th iteration, while the PSO analysis reaches its convergence value in the 40th iteration. The capital cost value obtained by the WHO analysis is 198,363.05 with a total of 772 PV units, a total of 1 unit of WT, and a total of 54 batteries.